Optimization of Liability for Companies That Do Not Implement Corporate Social Responsibility - Jeremy Samuel Pangkey Sondakh; Masykur, M. Hamidi; Widhiawati, Dyah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
In the context of the global economy, the implementation of Corporate Social Responsibility (CSR) not only serves as a moral responsibility, but has also become a legal obligation in various jurisdictions, including Indonesia. Indonesian regulations show inconsistencies in the use of CSR terms, scope, and enforcement mechanisms, as reflected in Law No. 40/2007 on Limited Liability Companies (UUPT) and Law No. 25/2007 on Capital Investment (UUPM). The UUPT limits CSR obligations to companies engaged in natural resources, while the UUPM requires CSR for all investors, regardless of business sector. This lack of synchronization creates a legal loophole that allows companies outside the natural resources sector to avoid CSR obligations. In addition, the sanction mechanism for companies that do not implement CSR is still weak, so compliance with this regulation tends to be low. This research aims to analyze the optimization of liability for companies that do not implement CSR in Indonesia through a normative juridical approach. The main findings show that legal uncertainty in CSR regulations has an impact on ineffective implementation and is often only symbolic. Some companies still consider CSR as a mere image strategy, with no real impact on society and the environment. Therefore, more stringent regulatory harmonization and more effective law enforcement mechanisms are needed. Policy revisions, strengthening sanction mechanisms, and increased supervision by relevant authorities can improve corporate compliance with Corporate Social Responsibility (CSR).